Systematic study of short circuit activation on the performance of PEM fuel cell - Zhang, Caizhi (2022)
During the operation of proton exchange membrane fuel cell (PEMFC), it always suffers from reversible performance loss caused by the oxidation of platinum catalyst on its electrode, which reduces the electrochemical active surface area. Short circuit method has been found to improve the performance of fuel cells by stripping of oxides and other adsorbed species from platinum, which needs systematical understanding the effective parameters of short circuit method on fuel cell performance. In this paper, the effects of different short circuit activation parameters (duration, interval, cycles, cut-off voltage, operating current) are carefully studied and analyzed during short circuit operations. In addition, the mechanism revealing how relevant parameters influence short circuit activations is deeply analyzed. The results show that five groups of activation parameters have obvious influence on the activation of fuel cell, indicating that the short-circuit activation effect can be optimized. Among these parameters, the short-circuit duration parameter have the greatest impact on activation, because the platinum hydroxides and oxides is gradually removed during short-circuit duration and results in a larger effective surface area of the platinum catalyst for the electrochemical reaction. However, the smallest impact is short-circuit interval. Another finding is that the five activation parameters are not independent, so the optimal activation parameter value needs to be analyzed in combination with the operating conditions. Finally, according to the activation principle, selection of appropriate short circuit activation parameters for application are proposed to further improve performance and fuel utilization by considering the safety of the stack.